Leadership, Learning and Teaching Practice in Higher Education : A 2016-2023 Bibliometric Review. - Adams, Donnie; Moosa, Visal (Journal of University Teaching & Learning Practice v.21 n.5 https://doi.org/10.53761/4fd9xn32, 2024)
The Journal of University Teaching and Learning Practice (JUTLP) has now published its twentieth annual volume, maintaining a record of publication for two decades now. This year, on the occasion of the journal's 20th annual volume, we seek to identify the distinctive contributions and influence of JUTLP as a research journal and how that influence has changed over time. This review has two broad purposes. First, it intends to empirically document the scholarly publications that has accumulated in JUTLP over its two decades of publication. Second, we seek to identify the noteworthy contributions that JUTLP has made to the field of leadership, teaching and learning practice in the higher education environment. This review is based on the analysis of 403 articles published in JUTLP between 2016 and 2023. Bibliographic data (e.g., authors, title, abstract, keywords, citations) in these articles were analysed using a bibliometric analysis method comprising of descriptive statistics, document citation and co-citation analysis, author co-citation analysis and keyword analysis. The review yields an empirically grounded findings on JUTLP 'corpus of knowledge' that provides useful indications and recommendations for the journal's future development. [Author abstract]